2020
DOI: 10.3847/2041-8213/aba534
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Active Galactic Nuclei in the Quenching of Massive Galaxies in the SQuIGG E Survey

Abstract: We study the incidence of nuclear activity in a large sample of massive post-starburst galaxies at z ∼ 0.7 selected from the Sloan Digital Sky Survey, and identify active galactic nuclei based on radio continuum and optical emission lines. Over our mass range of 10 10.6 −10 11.5 M , the incidence of radio activity is weakly dependent on stellar mass and independent of stellar age, while radio luminosity depends strongly on stellar mass. Optical nuclear activity incidence depends most strongly on the D n4000 li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 63 publications
6
39
2
Order By: Relevance
“…Furthermore, the details of exactly how, or indeed if, these AGNs impact upon the evolution of their host galaxies remain controversial and uncertain (e.g. Husemann et al 2016;Villar-Martín et al 2016;Maiolino et al 2017;Harrison 2017;Cresci & Maiolino 2018;Perna et al 2018;Rosario et al 2018;Baron et al 2018;Scholtz et al 2018Scholtz et al , 2020do Nascimento et al 2019;Brownson et al 2020;Yesuf & Ho 2020;Greene et al 2020;Bluck et al 2020;Bischetti et al 2020). Building a multiwavelength quasar survey to address these questions is the focus of the Quasar Feedback Survey, which we introduce here.…”
mentioning
confidence: 99%
“…Furthermore, the details of exactly how, or indeed if, these AGNs impact upon the evolution of their host galaxies remain controversial and uncertain (e.g. Husemann et al 2016;Villar-Martín et al 2016;Maiolino et al 2017;Harrison 2017;Cresci & Maiolino 2018;Perna et al 2018;Rosario et al 2018;Baron et al 2018;Scholtz et al 2018Scholtz et al , 2020do Nascimento et al 2019;Brownson et al 2020;Yesuf & Ho 2020;Greene et al 2020;Bluck et al 2020;Bischetti et al 2020). Building a multiwavelength quasar survey to address these questions is the focus of the Quasar Feedback Survey, which we introduce here.…”
mentioning
confidence: 99%
“…The majority of these 111 galaxies were selected as BOSS ancillary targets because their ugriz or WISE colors resembled those of high-redshift quasars or LRGs. Several others were selected because they had matches in the Chandra Source Catalog (Evans et al 2010) or the FIRST radio survey (Becker et al 1995, see also Greene et al 2020). Galaxies with non-CMASS target flags tend to be slightly brighter and lie at lower redshifts than the median of the full SQuIGG LE sample.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Each panel is colored by a different physical parameter, and our post-starburst color cuts are shown by the solid black lines. While f burst , t q , Greene et al (2020).…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tracing the features of active galactic nuclei (AGN) activity across cosmic time has highlighted more evidence of co-evolution. For example, total AGN accretion rate density is highly correlated with changes in star-formation rate (SFR) density (Madau & Dickinson 2014;Delvecchio et al 2014;Aird et al 2015); the effect of AGN on their host galaxies in the form of feedback is associated with the quenching of star formation (Di Matteo et al 2005;Fabian 2012;Greene et al 2020); and feedback could also explain the observed bi-modality in colour-magnitude and colour-mass space (Baldry et al 2004; ★ E-mail: klb69@leicester.ac.uk Martin et al 2007;Schawinski et al 2014).…”
Section: Introductionmentioning
confidence: 99%